Aussagepotentiale historischer Witterungstagebücher - das Jahr 1700 im Spiegel der Aufzeichnungen von Friedrich Hoffmann aus Halle - Glaser, Rüdiger; Gudd, Martin (ERDKUNDE, 1996)
This is the first climatological analysis of the weather diary kept by FRIEDRICH HOFFMANN of Halle for the year 1700, discussing both the methodological aspects and the contents of this journal. Based on this single source descriptively statistical and synoptic methods are applied far meaningfully characterizing the course of the weather. The overall weather situation in 1700 was contrary to that of the preceding cold phase with wet and cool summers and cold winters so typical of the period of the late Maunder Minimum. At Halle/Saale it was characterized by moderate winter weather and a pronounced summer heat, which for the first time in many years gave rise to sometimes euphoric evaluations of the overall living conditions, mainly so because the mild weather lead to a very good harvest and income situation. The weather situation of 1700 closely resembled that of a present normal year.